Unified gated basis modulation for agricultural virtual-to-real translation - Ruofei Ma; Xianglei Liu; Yi Zhang; Yuefeng Du; Lei Liu; Mingwei Du; Zhiqiang Guo (Computers and Electronics in Agriculture, 2026)

Orchestrating triacylglycerol biosynthesis and hydrolysis via synthetic genetic circuits enhances spinosad production in Streptomyces albus - Xiaochen Li; Ruofei Guo; Chanjuan Jiang; Ran Liu; Ji Luan; Hailong Wang (Bioresource Technology, 2026)

Mechanisms of extreme rainfall partitioning in contour ridge system: A modified SCS-CN method incorporating microtopographic and ridge geometry effects - Juan An; Guohui Li; Ruofei Liu; Yuanzhi Wu; Xiyuan Wu; Rui Zhang; Yao Zhao (Soil and Tillage Research, 2026)

Stepwise extraction of silicon and aluminum from nitric acid leach residue via sodium carbonate roasting and leaching - Fang Chen; Xue Ma; Lijun Jiang; Ruofei Du; Liangfeng Li; Laibao Liu; Xia Li; Bingyan Fan (Hydrometallurgy, 2026)

A multi-view depth-camera point cloud processing pipeline for pre-harvest maize stand counting - Ruofei Ma; Yuefeng Du; Lei Liu; Dafang Guo; Linze Wang; Du Chen; Zhenghe Song (Biosystems Engineering, 2026)

Nano-biochar enhances energy taxis of Shewanella oneidensis MR-1 and the bio-utilization of minerals and Cr(VI) - Tianao Zhou; Min Li; Guangfei Liu; Huali Yu; Lecheng Liu; Ruofei Jin; Ziyi Zhang (Journal of Cleaner Production, 2026)

From firm to soft: Maturity-driven mechanical damage behavior of apples - Zixu Chen; Linlong Jing; Ruofei Liu; Huawei Yang; Linlin Sun; Xinpeng Cao; Yongxian Wang; Shenghui Fu; Hongjian Zhang; Jinxing Wang (Postharvest Biology and Technology, 2026)

A 1DCNN-SENet-LSTM model for UGW-based automatic evaluation of grouting void location in post-tensioned concrete structure - Ruofei Liu; Longguan Zhang; Junfeng Jia; Shengli Li; He Guo; Binli Guo (Engineering Structures, 2025)

Photothermally responsive conductive hydrogels for dual-mode self-sensing soft actuators - Chengnan Qian; Ping Guo; Ruofei Wang; Xuanzi Luo; Yang Yu; Lin Cheng; Aiping Liu (Chemical Engineering Journal, 2025)

Microbial inoculants addition increases microbial necromass but decreases plant lignin contribution to soil organic carbon in rice paddies - Quanyi Hu; Xuelin Zhang; Ziwei Zhang; Ruofei Wang; Cheng Feng; Yingxin Xie; Shaojie Chen; Tianqi Liu (Soil and Tillage Research, 2025)

Road performance and chemical evolution of aged asphalt subjected to intense ultraviolet radiation and large temperature fluctuations - Zewen He; Jiuguang Geng; Wenhui Zhao; Jianwei Liu; Cong Qi; Ruofei Qi; Lu Huang (Fuel, 2025)

Revealing the excellent catalytic combustion ability of Cu1.5Mn1.5O4 (222) crystal facet with octahedrally coordinated Mn(Ⅳ)O6 site - Jian Deng; Chunhao Wang; Shenggui Ma; Chengchao Liu; Yongtao Zheng; Haipeng Chen; Ruofei Chen; Siyu Wei; Shanbi Peng; Xia Jiang (Journal of Environmental Chemical Engineering, 2025)

Design, bioactivity and mechanism of N′-phenyl pyridylcarbohydrazides with broad-spectrum antifungal activity - Yuhao Zhang; Bohang Zhou; Pengan Wei; Le Liu; Ruofei Bai; Yiwei Wang; Le Zhou (Molecular Diversity, 2025)

Impact of steel slag, gypsum, and coal gangue on microbial immobilization of metal(loid)s in non-ferrous mine waste dumps - Ruofei Li; Jun Yao; Jianli Liu; Shun Jiang; Geoffrey Sunahara; Robert Duran; Miaomiao Li; Houquan Liu; Chuiyun Tang; Hao Li; Bo Ma; Bang Liu; et al. (Journal of Hazardous Materials, 2024)

Remediation of arsenic- and nitrate-contaminated groundwater through iron-dependent autotrophic denitrifying culture - Jia-Bo Liu; Hongbin Zhang; Hefei Wang; Banghui He; Huixuan Wang; Ruofei Jin; Tian Tian (Environmental Research, 2024)

Treating reverse osmosis brine of petrochemical wastewater using preparative vertical-flow electrophoresis (PVFE) with multi-objective optimization by response surface method - Rongbo Chen; Tian Tian; Ruofei Jin; Ze Liu; Wang Fu; Qiuyan Ji; Jiti Zhou (Environmental Science and Pollution Research, 2024)

Bioindicator responses to extreme conditions: Insights into pH and bioavailable metals under acidic metal environments - Ruofei Li; Jun Yao; Jianli Liu; Geoffrey Sunahara; Robert Duran; Beidou Xi; Zozo El-Saadani (Journal of Environmental Management, 2024)

Unraveling assemblage of microbial community dwelling in Dabaoshan As/Pb/Zn mine-impacted area: A typical mountain mining area of South China - Jian-li Liu; Jun Yao; Ruofei Li; Houquan Liu; Jun-jie Zhu; Geoffrey Sunahara; Robert Duran (Science of The Total Environment, 2024)

Preparation of ceramsite using solid residue from anaerobic digestion of waste activated sludge and its enhancing effect on catalytic ozonation - Qiang Zheng; Qiuyan Ji; Tian Tian; Ruofei Jin; Ze Liu; Wang Fu; Jiti Zhou (Environmental Research, 2024)

Aromatics production from relay catalytic pyrolysis of cow manure using Ru/C and ZSM-5 dual catalysts synthesized from coal gasification fine slag - Ruofei Wu; Peng Lv; Bin Liu; Yonghui Bai; Jiaofei Wang; Juntao Wei; Weiguang Su; Guangyu Xu; Weina Bao; Guangsuo Yu (Journal of Environmental Management, 2023)

Alkaline-thermal hydrolysate of waste activated sludge as a co-metabolic substrate enhances biodegradation of refractory dye reactive black 5 - Xin Li; Tian Tian; Tiantian Cui; Baocun Liu; Ruofei Jin; Jiti Zhou (Waste Management, 2023)

Microbial metabolic activity in metal(loid)s contaminated sites impacted by different non-ferrous metal activities - Hao Li; Jun Yao; Ning Min; Geoffrey Sunahara; Jianli Liu; Miaomaio Li; Bang Liu; Wancheng Pang; Ying Cao; Ruofei Li; Robert Duran (Journal of Hazardous Materials, 2023)

Ubiquitinomics revealed disease- and stage-specific patterns relevant for the 3PM approach in human sigmoid colon cancers - Hua Yang; Na Li; Liang Chen; Lei Zhou; Yuanchen Zhou; Jixiang Liu; Wenshuang Jia; Ruofei Chen; Junwen Su; Lamei Yang; Xiaoxia Gong; Xianquan Zhan (EPMA Journal, 2023)

Facile preparation of coprecipitates between iron oxides and dissolved organic matter for efficient Fenton-like degradation of norfloxacin - Huali Yu; Guangfei Liu; Lingyu Shen; Ruofei Jin; Jiti Zhou; Haiyan Guo; Lianfeng Wang (Journal of Hazardous Materials, 2023)

5300‐Year‐old soil carbon is less primed than young soil organic matter - Jiao Su; Haiyang Zhang; Xingguo Han; Ruofei Lv; Li Liu; Yong Jiang; Hui Li; Yakov Kuzyakov; Cunzheng Wei (Global Change Biology, 2023)
Soils harbor more than three times as much carbon (C) as the atmosphere, a large fraction of which (stable organic matter) serves as the most important global C reservoir due to its long residence time. Litter and root inputs bring fresh organic matter (FOM) into the soil and accelerate the turnover of stable C pools, and this phenomenon is termed the “priming effect” (PE). Compared with knowledge about labile soil C pools, very little is known about the vulnerability of stable C to priming. Using two soils that substantially differed in age (500 and 5300 years before present) and in the degree of chemical recalcitrance and physical protection of soil organic matter (SOM), we showed that leaf litter amendment primed 264% more organic C from the young SOM than from the old soil with very stable C. Hierarchical partitioning analysis confirmed that SOM stability, reflected mainly by available C and aggregate protection of SOM, is the most important predictor of leaf litter‐induced PE. The addition of complex FOM (i.e., leaf litter) caused a higher bacterial oligotroph/copiotroph ( K ‐/ r ‐strategists) ratio, leading to a PE that was 583% and 126% greater than when simple FOM (i.e., glucose) was added to the young and old soils, respectively. This implies that the PE intensity depends on the chemical similarity between the primer (here FOM) and SOM. Nitrogen (N) mining existed when N and simple FOM were added (i.e., Glucose+N), and N addition raised the leaf litter‐induced PE in the old soil that had low N availability, which was well explained by the microbial stoichiometry. In conclusion, the PE induced by FOM inputs strongly decreases with increasing SOM stability. However, the contribution of stable SOM to CO 2 efflux cannot be disregarded due to its huge pool size.

Effects of sludge lysate for Cr(VI) bioreduction and analysis of bioaugmentation mechanism of sludge humic acid - Hongling Chen; Ruofei Jin; Guangfei Liu; Tian Tian; Chen Gu; Jiti Zhou; Defeng Xing (Environmental Science and Pollution Research, 2019)

Enhanced bioreduction of nitrobenzene by reduced graphene oxide materials: effects of surface modification and coexisting soluble electron shuttles - Guangfei Liu; Bin Dong; Jiti Zhou; Jing Wang; Ruofei Jin; Juanjuan Li (Environmental Science and Pollution Research, 2017)

Microbial synthesis of bimetallic PdPt nanoparticles for catalytic reduction of 4-nitrophenol - Ya Tuo; Guangfei Liu; Bin Dong; Huali Yu; Jiti Zhou; Jing Wang; Ruofei Jin (Environmental Science and Pollution Research, 2017)

Accelerated removal of Sudan dye by Shewanella oneidensis MR-1 in the presence of quinones and humic acids - Guangfei Liu; Jiti Zhou; Qiuyan Ji; Jing Wang; Ruofei Jin; Hong Lv (World Journal of Microbiology and Biotechnology, 2013)

Improved selective extraction of 3,3′-dichlorobenzidine by molecularly imprinted polysiloxane microspheres - Yuanying Hu; Ruofei Hu; Qingzeng Zhu; Jinhua Zhan; Hui Liu; Bingjian Yao (Environmental Chemistry Letters, 2012)

Site-directed mutagenesis of substrate binding sites of azoreductase from Rhodobacter sphaeroides - Guangfei Liu; Jiti Zhou; Jing Wang; Bin Yan; Jingmei Li; Hong Lu; Yuanyuan Qu; Ruofei Jin (Biotechnology Letters, 2008)